Peranan Guru Dalam Meningkatkan Nilai Karakter Disiplin Dan Kejujuran Siswa - Putry Julia; Ati Ati (Jurnal Dedikasi Pendidikan, 2019)
Research on the Role of Teachers in increasing the character value of discipline and honesty of students in lampeunuerut primary school on 27th, 2017 has been carried out. Formulation of the problem raised in this study The purpose of this study is to know the role of the teacher in improving the character value of discipline and honesty of students at SD Unggul Lampeunerut. The research method used is a qualitative approach with descriptive quantitative research. The results of the study showed that 83% of the teachers did not agree and had an effort to improve the karate discipline and honesty of the students while only 17% agreed to do so. Teacher conclusions have a very large role in the role of teachers in improving the character value of discipline and honesty of students at SD Unggul Lampeunerut